Herpes zoster in a 3-month-old infant without clinically overt maternal chickenpox. - Jasim, Z.F.; Woo, W.K.; Bingham, E.A. (European Journal of Pediatric Dermatology, 2003)
Infantile herpes zoster is rare and usually follows maternal varicella (chickenpox) infection during pregnancy. The effect of maternal chickenpox infection on the foetus could be severe and may depend on the stage of pregnancy. We report a case of infantile herpes zoster infection affecting the left C8-T1 dermatomes in a 3 month old infant. The mother was exposed to chickenpox during the 35th week of pregnancy but had no evidence of overt clinical chickenpox infection during pregnancy. Moreover, maternal varicella IgG antibodies were present during the 36th week of pregnancy indicating that the mother was immune to varicella zoster virus.